Cancer research in Latin America, 2014-2019, and its disease burden - Lewison, Grant (2021)
There is little available information on cancer research overall in Latin American and Caribbean countries, and on its relationship with the disease burden from cancer, which is increasing as a proportion of the total. We identified cancer research papers in the Web of Science from 2014-19. Outputs of the region on anatomical cancer sites were compared with the relative disease burden from these cancers. Outputs of individual countries were compared with their wealth and their disease burden from cancer. Their usage and impact on other researchers were determined from U2, a new usage indicator, citation counts over three years (C0-2), and the impact factor of the journals in which they were published (JIF). In 2014-19, Brazil, Chile and Uruguay published twice the amounts expected from the Latin American trend-line, but much less than European countries, relative to their Gross Domestic Products (GDPs). Most countries under-researched cancer relative to its burden. Lung, pancreatic and oesophageal cancers were relatively neglected. Less populous countries' research was of high impact, principally due to international collaboration with larger nations. Latin American research funding was dominated by the public sector. Current research orientation and funding is insufficient to combat the growing cancer burden in Latin America. This reflects the lack of research funding overall, relative to the countries' GDPs. The paucity of private-non-profit support needs to be addressed with policies to encourage public donations, and the endowment of foundations. There is also a need to improve the infrastructure for clinical trials.